Retroperitoneoscopic surgery with extracorporeal uretero-ureteral anastomosis for treating retrocaval ureter - Tobias-Machado,M. (2005)
We present a case of retrocaval ureter featuring laparoscopic technique treatment using extraperitoneal access and extracorporeal suture of the ureteral stumps. Surgical time was 130 minutes, and the anastomosis was performed in 40 minutes. There were no intra- or postoperative complications, and the patient was discharged from hospital on the second postoperative day. The medium-term outcome featured similar results to pure laparoscopic technique. We conclude that this technical variation for treatment of retrocaval ureter makes the procedure easier and provides a drastic reduction in surgical time, without compromising the minimally invasive aspect of this kind of approach.